Die Stadt als Architektur. - Wolfrum, Sophie; Janson, Alban (Birkhäuser, 2019)
Architektur ist die Kunst, Räume zu artikulieren. Auch für den Maßstab der Stadt, von der Türschwelle bis zur Region, geht es um die Architektur urbaner Räume. Diese sind Gegenstand des architektonischen Entwurfs, der ein Repertoire spezifischer Mittel schöpferisch einsetzt, so dass wir Städte als räumlich gestaltet erleben. Dieses architektonische Repertoire wird hier beschrieben. Entwurf und urban design finden wieder Eingang in die Urbanistik.

Architecture has always been engaged in a dialogue with its context - a relationship often dominated by tension. The architectural avant-garde in particular is commonly understood in its opposition to the existing metropolitan terrain: it positioned the form of the individual building against an - assumed - urban formlessness. The publication explores this dichotomy and analyzes the works of important urbanists, ranging from August Endell, Karl Scheffler, Ludwig Hilberseimer and Reyner Banham to Rem Koolhaas and Bernard Tschumi. Thus "The Good Metropolis" develops a theoretical and historical framework for understanding the complex relationship between architecture and the city.
Keywords: Stadtplanung; Städtebau; Architektur; Urbanität